Diagnóstico del sistema de gestión de seguridad y prevención de riesgos del trabajo según el sistema de auditorías de riesgos del trabajo (SART) en la empresa florícola agrícola El Rosario Agrirose CIA. LTDA. 2014-2015. Propuesta de un sistema de gestión en seguridad y prevención de riesgos del trbajo. - Uribe Campaña, José Eduardo (2015)
“El Rosario “Agrícola Cía. Ltda. is a company that produces fresh flowers from 1998 in Cotopaxi province, Latacunga canton. This place is located in Pastocalle. Actually, it has a population about 120 employees who work in a cultivation place of 18 hectares. Considering that it is a company which is legally established, it has legally obligations in terms of the fulfillment of the Ecuadorian legislation labor in occupational security and health. It is so that the Resolution of the Directing Council of the Ecuadorian Social Security Institute provides in the article 9 that the organizations must implement a system of security and health management in the job, which respond to the technical legal requirements of the Auditing system of the risks work. The present research work has considered as an objective to diagnostic the actual situation in the organization, based on the fulfillment of the technical legal requirements SART. It is going to be done through an objective investigation, resulting the fulfillment of the 21%. With these results, the researcher presents the proposal of a system of management which responds to the legal demands and let to diminish the probability of possible penalties or fines by the people who control it. In fact, it will permit to control the inherent risks of the floricola activities.